Social Conflict, Identity Boundaries, and Resource Competition: The Alas–Batak Case in Southeast Aceh (1950–1970) - Ridho, Adly Husaini; Abdullah, Munawiah; Ahmad, Muhammad Yunus; Mukhtar, Marduati (Jurnal Sosiologi Agama Indonesia (JSAI), 2026)
This study examines the social conflict between the Alas and Batak communities in Kuta Batu, Southeast Aceh, during the period 1950–1970. The research aims to analyze the underlying causes, the dynamics of conflict escalation, and the forms of conflict resolution that emerged within the local context. A qualitative descriptive approach was employed, drawing on in-depth interviews with seven informants and supported by documentary analysis. Data were analyzed through thematic coding and triangulation to reconstruct the historical process of conflict. The findings indicate that the conflict developed through the interaction of economic imbalance, identity formation, and weak institutional regulation. Differences in agricultural productivity were perceived as unequal access to resources, generating collective resentment. As competition intensified, ethnic and religious identities became more salient, reinforcing group boundaries and contributing to polarization. The absence of effective dispute management allowed tensions to escalate into violence, resulting in forced migration and the persistence of collective trauma. Conflict resolution efforts were largely informal and temporary, focusing on short-term mediation rather than structural transformation. As a result, the conflict was not fully resolved but instead left unresolved tensions embedded in social memory. The study highlights that social conflict in multiethnic societies is closely linked to the management of social change, resource distribution, and institutional capacity. These findings contribute to the understanding of conflict processes in local contexts and offer insights for developing more sustainable approaches to conflict prevention and reconciliation.